Towards a Sustainable Agriculture Development Based on the Field Vulnerability Evaluation in Miandoab Region, Iran - Vaziri, Maryam; Mahmoudi, Shahla; Shahbazi, Farzin; Masihabadi, Mohammad Hasan; Rezaei, Hossein (Nexo Revista Científica, 2022)
Exploring the agro-ecological limits is necessary in sustainable agriculture development. Soil contamination and erosion are two main indices in land vulnerability evaluation. Raizal and Pantanal models within MicroLEIS DSS, the Ero&Con package, were established in identification of vulnerable areas due to erosion and contamination risks, respectively. This study was performed in Miandoab region under different land-use scenarios with approximately 5269 ha extension in the North-West of Iran (west Azarbaijan). The extracted morphological and analytical data from 62 soil profiles representative of the study area were used as basic information. A total of 17 land unites were then classified according to the Geopedologic approach. The benchmark soil profiles were categorized as Typic Torripsamments, Typic Haploxerepts, Typic Haplocambids and Typic Haplargids. The results taken by using the aforementioned models were presented as an attainable mode whereas the management practices were not mentioned. The application of Raizal model revealed that the water erosion has less impact than wind erosion on vulnerability classes whereas climate change will result extremely high vulnerable area in the future. In terms of soil contamination risks resulted by Pantanal model, phosphorous risks were classified in V2 (23%) and V4 (77%). Also, heavy metal and nitrogen as well as pesticide contamination vulnerability risks were classified as V3 and V4. Since there was no different in classes when cultivating maize and wheat, the attainable vulnerability classes are equal with the actual ones. Overall, this research demonstrates that application of models increase our understanding about the behavior of soil and landscape interactions.